HUBUNGAN POWER OTOT TUNGKAI DENGAN LARI JARAK PENDEK 100 METER SISWA PUTERA O2SN SMP ANNUR KOTA PEKANBARU - Firdaus, Riki; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the observation of the authors on O2SN students of ANNUR Junior High School Pekanbaru, the authors found some problems in the O2SN athletes of SMP ANNUR Pekanbaru City showed that the result of the short 100 meter sprint obtained by the students is still not good, it may be due to the physical condition of the less trained students to move quickly. This study aims to determine the Relationship of Limb Muscle Power to Running Short Distance 100 Meter Student Son O2SN SMP ANNUR Pekanbaru City. The sample of this research is O2SN Student of Junior High School ANNUR Pekanbaru City which is 7 people. The sampling technique was taken by (total sampling) or sampling technique in full of O2SN Student of Junior High School ANNUR Pekanbaru City which amounted to 7 people. Result of correlation of O2SN Student Student of Junior High School of ANNUR Pekanbaru City where analysis between Limb Muscle Power (X1) with 100 meter Short Run Distance where rtab at significant level Î± (0,05) = 0,811, mean rhitung (0,944)> rtab (0,811). meaning the hypothesis is accepted and there is a strong relationship between Limb Muscle Power with Running Distance Short 100 meters Student Son O2SN SMP ANNUR Pekanbaru City.Keywords: Limb Muscle Power, Running Short Distance.